2023
DOI: 10.1088/1361-6501/acaf96
|View full text |Cite
|
Sign up to set email alerts
|

Time transfer with BDS-3 signals: CV, PPP and IPPP

Abstract: The third phase of BeiDou navigation satellite system (BDS-3) was officially commissioned on July 31, 2020. In this study, we make a comprehensive evaluation of BDS-3 time transfer with the B1I, B3I, B1C and B2a measurements. The muti-path errors and noises of different BDS-3 ranging signals are analyzed to illustrate characteristic of the code observations firstly. Then dual-frequency ionosphere-free linear combinations of BDS-3 B1I&B3I and B1C&B2a measurements are used to achieve time transfer. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…From equation (10), it is noted that the receiver and satellite clock offsets are condensed in ∆ tk i for simplicity. All the unknown parameters in equation (10) are expressed in equation (11). Here, δd k,(B,E) j denotes the pseudorange interfrequency bias on the j th frequency, λ 1…”
Section: Ppp-ar Implementation Using Osbsmentioning
confidence: 99%
See 1 more Smart Citation
“…From equation (10), it is noted that the receiver and satellite clock offsets are condensed in ∆ tk i for simplicity. All the unknown parameters in equation (10) are expressed in equation (11). Here, δd k,(B,E) j denotes the pseudorange interfrequency bias on the j th frequency, λ 1…”
Section: Ppp-ar Implementation Using Osbsmentioning
confidence: 99%
“…BDS-3 comprises satellites in three distinct orbits, namely the medium The BDS-3 multi-frequency signals, coupled with the three kinds of satellites in MEO, IGSO and GEO orbits, are increasing the research dimension in the GNSS community. In both BDS-only and multi-GNSS constellations, a considerable volume of research has followed in different fields such as multipath [2,3], signal-to-noise ratio (SNR) [4], GNSS interferometric reflectometry [5,6], quality of BDS products [7,8], precise time transfer [9,10], and ambiguity resolution (AR) [11]. While multi-frequency and multi-constellation GNSS may be applied in such broad areas, the increase in signals itself complicates the treatment of biases in the formulated observables.…”
Section: Introductionmentioning
confidence: 99%
“…is the frequency value of a satellite system; I s,sys r,1 is the tilted path ionospheric delay for the first frequency; d sys r,i and d s,sys i denote the pseudo-range hardware delay between the receiver antenna and the signal processor and between the signal generation and the satellite antenna launch for a system frequency, respectively; b sys r,i and b s,sys i denote the phase hardware delay between the receiver antenna and the signal processor and between the signal generation and the satellite antenna launch for a system frequency; λ i is the i frequency wavelength; N s r,i is the carrier phase circumference ambiguity; e s,sys r,i and ε s,sys r,i denote the observation noise and unmodeled error for the frequency pseudo-range and carrier phase observations. IF is often used in PPP to eliminate the ionospheric first-order term, thus reducing the influence of ionospheric delay on GNSS observations, and its observation equation can be written as follows [33][34][35]:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The BDS-3 wide-area positioning performance was investigated, which demonstrated that the PPP convergence time using B1C/B2a signals was significantly shortened compared to the B1I/B3I signals [16]. The PPP time transfer was also investigated using the B1C/B2a signals, and the time links using B1C/B2a signals were shown to be more stable [17]. The BDS-3 new signals have been used in diverse precise data processing applications.…”
Section: Introductionmentioning
confidence: 99%